Challenges of lead leakage in perovskite solar cells. (24th August 2022) - Dou, Jing; Bai, Yang; Chen, Qi
Abstract : This review summarizes the latest research progress on strategies for lead leakage control in perovskite solar cells to facilitate the future development of efficient, stable, and environmentally friendly perovskite photovoltaic devices. Abstract : Solar energy is a promising energy source to resolve the expanded energy demand for global development. In recent years, perovskite solar cells (PSCs) have shown dramatic improvements, from device efficiency to operation lifetime. Their low-cost and simple preparation process, tunable bandgap, and customizable applications give them promise for commercialization. Among the perovskite materials for photovoltaic application, the lead-halide perovskites have achieved the highest efficiency of 25.7%, which is much better than that of Sn-based (13.4%) and Ge-based (7.11%) PSCs, and at the same time, the best stability. However, the toxicity risk of the Pb element makes people question its commercial application. Pb-polluted soil could affect the growth of plants, and the contaminated water environment influences the health of fish and other aquatic animals. Pb will eventually accumulate in human body through the food chain, damaging the central nervous system and causing cardiovascular diseases. Laws and regulations for heavy metals are well established, and only if the Pb leakage risk can be controlled within a certain range can the commercial application of PSCs be considered safe and reliable. This review summarizes the pathway for Pb leakage and its impact on health and the environment. Especially, strategies for preventing Pb from leaking are discussed. Finally, we propose strategies for PSCs to achieve a good balance between high efficiency, long-term stability, and environmental protection.